EFFICIENCY OF APPLYING DIGITAL TECHNOLOGIES IN STOMATOLOGY (World Bulletin of Public Health, 2026)
The article examines the effectiveness of applying digital technologies in dentistry, highlighting significant improvements in diagnostic accuracy, acceleration of treatment processes, and patient care personalization. SD scanning, digital radiography, CAD/CAM systems, and robotic surgical technologies are being considered. The article highlights the main challenges facing the industry: high starting costs, data confidentiality issues, and the need for personnel training.